The Representation of Satirical Language in the Webtoon The Real Lesson: A Critical Discourse Analysis Based on Norman Fairclough’s Model : - Waode Ciciyawati Muhtar; Wityatmike Gede Mulawarman; Rusydi Ahmad; Kukuh Elyana (Raja Zulkarnain Education Foundation, 2026)
This study examines the representation of satirical language as a medium for social criticism in the webtoon The Real Lesson by Chae Yongtaek. This study was conducted as a literature review, utilizing primary data sources in the form of the webtoon text and secondary data sources from books, journals, and articles. This study employs a qualitative descriptive method using Norman Fairclough’s Critical Discourse Analysis (CDA) model. CDA, as theorized by Norman Fairclough, has three dimensions: text analysis, discourse practices, and sociocultural practices. The results of this study indicate that in the text analysis, the creator Chae Yongtaek, the writer of the webtoon The Real Lesson, employs four forms of irony manifested through negative-connoted diction, supported by transitive structures. In discourse practice, the satire is produced through intertextuality with real-life cases in South Korea, distributed via the Webtoon platform, and consumed through three decoding patterns: dominant, negotiated, and oppositional. In sociocultural practice, the satire represents social issues.